IMPLEMENTASI PROGRAM ART UNAIDS (UNITED NATIONS PROGRAMME ON HIV/AIDS) DALAM UPAYA PENANGANAN HIV/AIDS DI AFRIKA SELATAN TAHUN 2005-2012 - Mhd. Fikri Sulthoni; Yuli Fachri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This research analyzes UNAIDS effectiveness to handle HIV/AIDS in South Africa, especially along 2005 until 2012. South Africa is one of the biggest country whose high number of HIV/AIDS sufferer, which reaches 12 percent of its population total. South Africa has joined with UNAIDS since 2001 based on the assignment of UNGASS (United Nations General Assembly Special Session) on HIV/AIDS.In dealing HIV/AIDS in certain country, UNAIDS recommends numbers of programs. Related to South Africa, UNAIDS recommends ART. ART is a combination of treatment for HIV/AIDS patient by giving medicines and therapy. After the program was applied, the HIV/AIDS sufferer even increased. Therefore, this research will examine the causative factors, why ART program didn’t run effectively in South Africa.The datas were collected from many source like books, journals, and websites that can support this research. In this research, the researcher uses pluralism perspective to describe the effectiveness UNAIDS in South Africa. This research is supported by international organization theories. Efectivity concept is also provided to support this research.Keyword : UNAIDS, Effectiveness, UNGASS, ART Programme.